A RELAÇÃO DO EDIFÍCIO DE HABITAÇÃO DE INTERESSE SOCIAL COM A CIDADE, PERMEADO PELA LEGISLAÇÃO ESPECÍFICA - Teixeira, Catharina Christina (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The creation of legislation for Social Interest Housing (HIS) development in Sao Paulo came from the need to foster a legal framework for the city's housing policy in 1992. There were three main decrees from 1992 to 2016: decrees no. 31.601/1992, no. 44.667/2004 and no. 56.759/2016 along with debates about Municipal Master Plans. The latest two of them have also been influenced by the Statute of the City. The first two acts represented significant advancements regarding the configuration of housing clusters, by reducing large-scale residential development in favor of housing in central areas and the possibility of further development of precarious settlements. However, with each update, there has been a crescent loosening on regulation favoring the private sector, under allegations of a housing deficit and the need for provision of new units, in place of public action aimed at re-urbanization and at regulating land use, which meant a shift from the original intentions of the deed and the purposes of the city's housing policies.